Architectural problems of public and residential buildings in Kabul city - Hijratullah Hedayat (World Scientific Reports, 2023)
This article studies architectural problems of public and residential buildings in Kabul city of Afghanistan. The reasons behind substandard construction and design of buildings in Kabul city, the problems and dangers of these substandard buildings. In this article the reasons of substandard design of buildings are analyzed in detail and some solutions are given for these architectural mistakes and failures to avoid substandard construction of public and residential buildings and avoid dangers which may threaten residents’ life.